The Courtauld collection a vision for impressionism - Serres, Karen; Scherf, Angéline 19XX- (The Courteauld Gallery, 2019)
The Courtauld Collection: A Vision for Impressionism' accompanies a landmark exhibition at the Fondation Louis Vuitton in Paris exploring Samuel Courtauld's role as one of the great collectors of the twentieth century. The catalogue and exhibition showcase Courtauld's extraordinary collection, which will be on display in Paris for the first time in over sixty years.0One of the finest collections of Impressionism anywhere in the world was assembled by the English industrialist and philanthropist Samuel Courtauld (1876-1947). During the 1920s, Courtauld acquired seminal works by all of the major Impressionists, from Renoir's early masterpiece La Loge to Manet's last great work, A Bar at the Folies-Bergere. His collection grew to include such iconic works as Gauguin's great Tahitian nude Nevermore and one of Van Gogh's most famous paintings, Self-Portrait with Bandaged Ear. Courtauld was particularly devoted to Cezanne and put together the largest collection of his work in the United Kingdom, including the epic Montagne Sainte-Victoire with Large Pine and one of the celebrated Card Players. After a decade of collecting, Courtauld gave the majority of these remarkable works to establish The Courtauld Institute of Art and Gallery in London
Published on the occasion of the exhibition held at the Foundation Louis Vuitton, Paris, France, February 20-June 17, 2019
Keywords: Courtauld Institute of Art -- Courtauld Collection; Geschichte 1860-1900; Malerei; Plastik; Frankreich; Courtauld, Samuel / 1876-1947 / Art collections / Exhibitions; Courtauld, Samuel / 1876-1947; Courtauld (Samuel) Collection / (Priv.); Courtauld (Stephen) Collection / (Priv.); Courtauld Institute Gallery (London) / (Perm.); Art / Private collections / England / London / 20th century / Exhibitions; Impressionism (Art) / Exhibitions; Art / Private collections; Impressionism (Art); Exhibition catalogs; Essays; Illustrated works; Ausstellungskatalog -- Courtauld Gallery -- 20.02.2019-17.06.2019 -- London